1991
DOI: 10.1093/jn/121.8.1163
|View full text |Cite
|
Sign up to set email alerts
|

High Dietary Linoleic Acid Affects the Fatty Acid Compositions of Individual Phospholipids from Tissues of Atlantic Salmon (Salmo salar): Association with Stress Susceptibility and Cardiac Lesion

Abstract: For 16 wk Atlantic salmon (Salmo salar) post-smolts were fed practical-type diets that contained either fish oil (FO) or sunflower oil (SO) as the lipid component. Both diets contained adequate (n-3) polyunsaturated fatty acids (PUFA). All the phospholipids of heart and liver from SO-fed fish had increased levels of 18:2(n-6), 20:2(n-6) and 20:3(n-6); phosphatidyl choline (PC) and phosphatidyl ethanolamine (PE) also had increased 20:4(n-6). There was a general decrease in 20:5(n-3) in the phospholipids, reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
83
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(94 citation statements)
references
References 23 publications
10
83
1
Order By: Relevance
“…and decrease EPA and DHA levels in liver polar lipids in salmon smolts (Bell et al, 1991(Bell et al, ,1993. In the present trial, feeding salmon parr the rapeseed/linseed oil (VO) diet (rich in both 18:2n-6 and 18:3n-3) increased the levels of 18:2n-6 and total n-6PUFA but not AA, and increased 18:3n-3 but decreased DHA in both Atlantic salmon and brown trout.…”
Section: Discussionmentioning
confidence: 99%
“…and decrease EPA and DHA levels in liver polar lipids in salmon smolts (Bell et al, 1991(Bell et al, ,1993. In the present trial, feeding salmon parr the rapeseed/linseed oil (VO) diet (rich in both 18:2n-6 and 18:3n-3) increased the levels of 18:2n-6 and total n-6PUFA but not AA, and increased 18:3n-3 but decreased DHA in both Atlantic salmon and brown trout.…”
Section: Discussionmentioning
confidence: 99%
“…It is now known [4,7] that diets with an over high ratio of n-6/n-3 PUFA could exaggerate stress response in fish broodstock leading to cardiac pathologies. The involvement of essential fatty acids in broodstock fish and developing eggs and larvae and their fundamental involvement in stress reactions demands consideration of what constitutes an optimal or even desirable dietary ratio of n-6/ n-3 PUFA in broodstock.…”
Section: Discussionmentioning
confidence: 99%
“…Similar other trials with Atlantic salmon have shown that substitution of FO with SFO does not significantly affect growth (Bell et al, 1991(Bell et al, , 1996. However, Thompson et al (1966) found in two similar trials with Atlantic salmon that when SFO was used as the primary oil source, the experimental fish either grew significantly less or the same as those fed diet containing FO.…”
Section: Discussionmentioning
confidence: 89%
“…Attempts have been made at partially substituting or replacing fish oils with vegetable oils (Bell et al (1991(Bell et al ( , 1996, Bransden et al, 2003. ) Fish oil substitution must however be done such that the product quality in terms of long chain n-3 poly unsaturated fatty and (PUFA) content as well as the eating quality are not diminished.…”
Section: Introductionmentioning
confidence: 99%